An exceptional deal. Affirmative everyday action at the National University of Cuyo - Fernández Vavrik, Germán (Education Policy Analysis Archives, 2014)
The actors engaged in the accomplishment of a scholarship program at the University of Cuyo from Argentina deal with an insolvable tension, inherent to affirmative action policies. It is the tension between principles of equality and difference. Coming from Huarpes indigenous communities and from rural villages, the scholarship holders are described by the University authorities as people who deserve at the same time two kinds of treatment: a) a special treatment because of their origin and b) an impersonal treatment due to their status of students at a mass university. The program is an exceptional measure regarding equity policies in Argentina. It selects and categorises students according to a sociocultural criterium of origin instead of the traditional socioeconomic criterium. To understand how those newcomers are treated and how their experience is accounted for, the sociological inquiry is based on interviews, ethnography, audiovisual analyses as well as examination of University internal documents and legal ordinances.